2018
DOI: 10.1108/jpmd-09-2017-0086
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous residents’ perceptions towards tourism development: a case of Sabah, Malaysia

Abstract: Purpose This paper aims to investigate the perceptions of indigenous people towards tourism development and the factors that influence their perceptions of the economic, social and environmental impacts of tourism. Design/methodology/approach This study will focus on the perceptions of an aboriginal group indigenous to Malaysia, and draws upon a sample of 272 from the Lower Kinabatangan region of Sabah, Malaysia. Respondents were administered a questionnaire, the results of which were analysed by way of part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 59 publications
(139 reference statements)
0
14
0
Order By: Relevance
“…Existing literature has revealed various economic factors that are beneficial for the local residents like job opportunities, increase in income, business (Alrwajfah et al, 2019;Andereck et al, 2005;Boley et al, 2017;Choi and Sirakaya, 2006;Ko and Stewart, 2002;Nugroho and Numata, 2020), improves the standard of life (Adongo et al, 2017;Haralambopoulos and Pizam, 1996), etc. Almost all studies reported a positive relationship between perceived economic benefits and support for tourism development (Boley et al, 2017;Keogh, 1990;Ko and Stewart, 2002;L atkov a and Vogt, 2012;McGehee et al, 2002;Gursoy and Rutherford, 2004;Sharma et al, 2008;Nunkoo, 2015;Adongo et al, 2017;Latip et al, 2018;Stylidis and Terzidou, 2014). These advantages, however, are frequently joined by an expansion in the cost of living (Alrwajfah et al, 2019;Ko and Stewart, 2002;Nugroho and Numata, 2020), a general increase in the prices of goods and services (Alrwajfah et al, 2019;Andereck et al, 2005;Brunt and Courtney, 1999;Nugroho and Numata, 2020), rising property prices (L atkov a and Vogt, 2012; Nugroho and Numata, 2020), etc.…”
Section: Residents' Perceived Impacts Of Tourism and Their Attitudes Toward Tourism Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Existing literature has revealed various economic factors that are beneficial for the local residents like job opportunities, increase in income, business (Alrwajfah et al, 2019;Andereck et al, 2005;Boley et al, 2017;Choi and Sirakaya, 2006;Ko and Stewart, 2002;Nugroho and Numata, 2020), improves the standard of life (Adongo et al, 2017;Haralambopoulos and Pizam, 1996), etc. Almost all studies reported a positive relationship between perceived economic benefits and support for tourism development (Boley et al, 2017;Keogh, 1990;Ko and Stewart, 2002;L atkov a and Vogt, 2012;McGehee et al, 2002;Gursoy and Rutherford, 2004;Sharma et al, 2008;Nunkoo, 2015;Adongo et al, 2017;Latip et al, 2018;Stylidis and Terzidou, 2014). These advantages, however, are frequently joined by an expansion in the cost of living (Alrwajfah et al, 2019;Ko and Stewart, 2002;Nugroho and Numata, 2020), a general increase in the prices of goods and services (Alrwajfah et al, 2019;Andereck et al, 2005;Brunt and Courtney, 1999;Nugroho and Numata, 2020), rising property prices (L atkov a and Vogt, 2012; Nugroho and Numata, 2020), etc.…”
Section: Residents' Perceived Impacts Of Tourism and Their Attitudes Toward Tourism Developmentmentioning
confidence: 99%
“…These impacts comprise an increase in crime and drug use (Deery et al, 2012;Pizam, 1978), prostitution (Sharma et al, 2008), dislodging of residents and land-use problems (Unalan, 2013). From the existing studies, a positive relationship between social benefits and support for tourism development is found (Jaafar et al, 2017;Gursoy and Rutherford, 2004;Adongo et al, 2017;Latip et al, 2018;Stylidis and Terzidou, 2014) and also established a negative relationship between social costs and support for tourism development (Jaafar et al, 2017;Gursoy and Rutherford, 2004;Adongo et al, 2017).…”
Section: Residents' Perceived Impacts Of Tourism and Their Attitudes Toward Tourism Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The growth of ecotourism parallels rising concerns about environmental issues in protected areas (Benedetto et al, 2016;Xu & Fox, 2014;Latip et al, 2018). While previous investigations of ecotourism development and environmental issues in protected areas have found considerable variation in the environmental perceptions of visitors, it remains unclear whether and how these visitor environmental perceptions might affect their support for ecotourism development.…”
Section: Tourism Development and Environmental Issuesmentioning
confidence: 99%